ARK876: Construction Project Management / Faculty of Architecture, Planning & Surveying - UiTM, Faculty of Architecture, Planning & Surveying (Universiti Teknologi MARA (UiTM), 2023)
Students are introduced to basic management principles. Lectures and coursework will be given to enhance students understanding in the theory and practice of Project Management. Apart from lectures, a special programme called Integrated Simulation Project (ISP) will be organised involving students from 3 different disciplines namely architectural, quantity surveying and building. Simulation exercises based on given projects are conducted to tackle project issues, which are resolved through teamwork and understanding of the various disciplines mentioned.